A Comprehensive Review of the Most Devastating and Catastrophic Return of Fear and Uncertainty: The Covid-19 Crisis - Roomi, M Waheed (Disease and Health: Research Developments Vol. 7, 2025)
In 2019, the world witnessed the beginnings of a global pandemic in the form of a new respiratory illness. Covid-19, also known as coronavirus disease 2019, is a highly contagious infectious disease caused by the novel coronavirus “SARS-CoV-2”. Covid-19 is the news once again making headlines and announcing its comeback. It has had a profound impact since its December 2019 emergence from Wuhan, China. The 2019 outbreak was a turning point affecting nearly every country with varying degrees of devastating and catastrophic severity. It has led to significant worldwide mortality and morbidity causing millions of deaths and long-lasting health complications for many, directly or indirectly. The rapid spread worldwide, led to the World Health Organization calling it a “global pandemic” on March 11, 2020. It has reshaped the world’s healthcare systems, caused economic disruptions and forced significant changes in lifestyle. Since the beginning of the Covid-19 pandemic up until the end of 2024, there have been over 800 million globally confirmed cases. During the same period, the world-wide death rate was just over 7 million with 13 billion Covid-19 vaccinations administered globally. The scar left by Covid-19 is witnessed on the face of every individual and every sector of the economy. Anytime a viral outbreak has the potential to take hold, a containment strategy must be followed in order to keep it from becoming a pandemic. This study is a detailed presentation of the covid crisis. Covid-19 is a viral zoonotic disease which spreads from animals-to-humans and humans-to-humans. It is caused by the novel SARS-CoV-2 coronavirus. Covid-19 is an enveloped, positive-sense single-stranded RNA virus that attaches to the host cell through its spike protein which facilitates entry into the host cell via the ACE2 receptors. The virus primarily spreads through respiratory droplets of an infected person when coughing, sneezing or talking and can also spread via contact with contaminated surfaces. Asymptomatic or pre-symptomatic individuals can also spread the disease. Covid-19 has caused major social, economic, business and lifestyle disruptions. Covid-19 symptoms range from mild to severe and appear between 2-14 days after exposure. The most common symptoms include fever, cough, shortness of breath, fatigue, muscle or body aches, loss of taste or smell, headache, nausea or vomiting and diarrhea. In more severe cases, it can cause pneumonia, ARDS, organ failure and even death. A Covid-19 diagnosis is mainly done by polymerase chain reaction (PCR) - the gold standard of testing. Histologically, Covid-19 is responsible for many changes to the lungs, heart, kidneys, liver and GI tract. Symptoms lasting beyond the primary infection (“long-covid”) have shown to have a significant impact on an individual’s daily life. There are several factors that increase the risk of infection. Individuals who are over 60 versus younger individuals, individuals with comorbidities, those who are immunocompromised, those who smoke, use alcohol, lack exercise or are unvaccinated, all have a higher risk of infection. Infected individuals with underlying health conditions can experience a host of complications such as mild to severe organ impairment (heart, liver, kidney, brain), diabetes, dementia, neurological issues, GI issues, and hematological or muscular pain. The risk also increases for individuals who are lower on the socio-economic spectrum. One of the most prominent features of the Covid virus is its ability to mutate over time. This leads to the emergence of variants with different properties. Currently, there is no definite treatment for Covid-19. The Centers for Disease Control and Prevention (CDC) recommends the use of vaccines, antiviral drugs, immunomodulators, monoclonal antibodies and non-pharmaceutical interventions (wearing masks, social distancing, hand hygiene, quarantine, isolation) to reduce the transmission risk, prevent hospitalization and to avoid severe illness or death. The advent of highly efficacious vaccines using novel mRNA technology has seen the effects of the disease wane. The Covid-19 outbreak brought to light some very stark realities. It is abundantly clear there is no influence over animal biology, their disease reservoirs, the host type (bats, mosquitoes), virus mutation, etc. From a societal standpoint, there is no influence over social behavior (collective, individual), socio-economic disparities, age, gender, comorbidities or national resources. Looking at these factors alone, one can see the insurmountable task of controlling another outbreak. Covid-19 infection rates are slowing and the pandemic is giving way to an endemic. However, one question remains - how well prepared are we for the next major outbreak?